Multifactorial Predisposition Related with Scabies Among Islamic Student - Anisa, Fidya; Nurapandi, Adi; Kusumawaty, Jajuk (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Scabies is known as a contagious skin disease caused by mites that hide in the skin called sarcoptes scabiei var ectoparasites hominis and causes quite serious morbidity and severe bacterial infections. This bacteria easily breeds in damp or wet places, dense settlements and lack of sunlight such as Islamic boarding schools, dormitories and boarding schools. This study aims to analyze the factors related to the incidence of scabies in students at Islamic boarding schools. Method: The research design used was correlational analytic with a cross-sectional approach. The population in this study were all students who were experiencing and had a history of scabies at the Miftahul Amin Islamic Boarding School from November to January. The number of participants involved in this study was 50 people with a purposive sampling technique. The research instruments used were questionnaires on knowledge, attitudes, personal hygiene behavior, and environmental sanitation. The data were processed using SPSS software version 20 and analyzed using the chi square test and double logistic regression. Result: The results of the bivariate analysis showed that all variables had a relationship with the incidence of Scabies, namely knowledge (pvalue = 0.03), attitude (pvalue = 0.03), personal hygiene behavior (pvalue = 0.04) and environmental sanitation (pvalue = 0.03). While the multivariate analysis showed that environmental sanitation was the most dominant factor causing scabies with a pvalue = 0.006. Conclusion: There is a significant relationship between knowledge, attitudes, personal hygiene behavior and environmental sanitation with the incidence of scabies in students at Islamic boarding schools.